Third International Workshop on Real-Time Computing Systems and Applications : proceedings, October 30-November 1, 1996, Seoul, Korea / sponsored by Korea Information Science Society (KISS) in cooperation with IEEE Computer Society, IEEE Computer Society Technical Committee on Real-Time Systems. (1996)
Summary goes here